Neural substrates of risky decision making in individuals with Internet addiction. (October 2015) - Seok, Ji-Woo; Lee, Kyung Hwa; Sohn, Sunju; Sohn, Jin-Hun
Objective: With the wide and rapid expansion of computers and smartphones, Internet use has become an essential part of life and an important tool that serves various purposes. Despite the advantages of Internet use, psychological and behavioral problems, including Internet addiction, have been reported. In response to growing concern, researchers have focused on the characteristics of Internet addicts. However, relatively little is known about the behavioral and neural mechanisms that underlie Internet addiction, especially with respect to risky decision making, which is an important domain frequently reported in other types of addictions. Method: To examine the neural characteristics of decision making in Internet addicts, Internet addicts and healthy controls were scanned while they performed a financial decision-making task. Results: Relative to healthy controls, Internet addicts showed (1) more frequent risky decision making; (2) greater activation in the dorsal anterior cingulate cortex and the left caudate nucleus, which are brain regions involved in conflict monitoring and reward, respectively; and (3) less activation in the ventrolateral prefrontal cortex, an area associated with cognitive control/regulation. Conclusion: These findings suggest that risky decision making may be an important behavioral characteristic of Internet addiction and that altered brain function in regions associated with conflict monitoring, reward and cognitive control/regulation might be critical biological risk factors for Internet addiction.